James Bermúdez -Parallel Lines for Calibration of Non-Central Conical Catadioptric Cameras - Bermúdez, James (Jornada de Jóvenes Investigadores del I3A, 2022)
Parallel Lines for Calibration of Non-Central Conical Catadioptric Cameras